Spending or saving? Female empowerment and financial decisions in a matrilineal society - Ute Rink; Laura Barros (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2019)
This paper looks at household consumption and financial decisions made in a matrilineal society where women are traditionally the household financial managers. This culture was strongly altered by the British in the mid-19th century through Christian missionaries who proclaimed that the role of the household manager is ascribed to men and not to women. Using self-collected data of 650 individuals from the matrilineal state of Meghalaya, India, and exploring household's distance to the historical Protestant base in Cherrapunji, we find evidence that household where women are empowered spend more on welfare enhancing goods, such as food, but are less likely to have savings left at the end of the month. Our paper contributes to the literature by investigating how a historical shift in female empowerment, mostly driven by cultural norms, can have long-term effects on financial decisions.
Keywords: I3; O1; R20; Z1; 330; female empowerment; matrilineality; culture; savings; India; Protestant missions